ОРГАНИЗАЦИЯ СИСТЕМЫ РАННЕГО ВЫЯВЛЕНИЯ БОЛЬНЫХ АРТЕРИАЛЬНОЙ ГИПЕРТЕНЗИЕЙ И ДОСТУПНОСТЬ АНТИГИПЕРТЕНЗИВНЫХ СРЕДСТВ В ВОЛОГОДСКОЙ ОБЛАСТИ. ОПЫТ ИСПОЛЬЗОВАНИЯ КЛАСТЕРНОГО АНАЛИЗА - Г. Г. Рапаков; Г. Т. Банщиков (Архивъ внутренней медицины, 2013)
Arterial hypertensia (AH) is one of the most extensive circulatory system diseases. It represents a risk factor of more dangerous complications such as stroke, myocardial infarction, and arterial thrombosis. The existent sufficient quantity of antihypertensive drugs has not solved the problems of decrease of mortality as a consequence of complications, connected with AH. AH patients in the Vologda region were questioned about the accessibility of medicinal drugs and readiness to treatment. The level of satisfaction with the system and ensure the quality of their medicines was estimated. The use of regression method of analysis showed that the doubling of the general practitioners number lead to 49% increase of recognition of the amount of arterial hypertensia cases. Сluster analysis and thematic maps were used for AH of the municipalities. Authors think that decrease of mortality through AH disease complications is influenced by staffing of general practitioners, quality of drugs provision and information awareness for patients about AH treatment.